Patient risk factors for opioid‐related adverse drug events in hospitalized patients: A systematic review. Issue 3 (14th February 2022) - Yiu, Chin Hang; Vitharana, Nilru; Gnjidic, Danijela; Patanwala, Asad E.; Fong, Ian; Rimington, Joanne; Begley, David; Bugeja, Bernadette; Penm, Jonathan
Abstract: Introduction: Opioid utilization has increased fourfold over the past two decades among developed countries. Previous studies have found that opioid‐related adverse drug events (ORADEs) are strongly associated with adverse clinical outcomes in hospitalized patients. The Society of Hospital Medicine in the United States recently published a Consensus Statement regarding opioid safety and suggested that extra caution is needed when using opioids in patients with risk factors for ORADEs. This systematic review aimed to summarize common patient risk factors for ORADEs in hospitalized patients. Methods: Five databases were searched including Medline, Embase, Cochrane Central Register of Controlled Trials, International Pharmaceutical Abstracts, and Scopus. Search themes include opioids, adverse drug events, and acute care settings. Original full‐text studies that were published and identified patient risk factors for ORADEs in hospitalized patients were included. Results: A total of 16 observational studies were included, with only two studies considered as poor quality. Seven studies focused on severe ORADEs including over‐sedation and respiratory depression. Common patient risk factors for severe ORADEs included comorbidities (eg, sleep apnea and renal diseases), concurrent use of sedatives, and prior opioid exposure. Nine studies focused on a combination of general ORADEs and common patient risk factors included advanced age, male gender, comorbidities (eg, chronic obstructive pulmonary disease and neurologic disorders), concurrent use of sedating medications, and prior opioid exposure. Conclusions: Successful identification of patient risk factors for ORADEs summarized by this systematic review could benefit clinicians when deciding on the appropriateness of opioid therapy in hospital patients. Future studies could focus on developing a validated risk assessment tool based on these risk factors.